The effect of financial literacy on rural households insurance participation: evidence from farmers in southwest China. Issue 1 (2nd January 2023) - Liu, Wenzhen; Wang, Bin; Wang, Chuanyu; Han, Kefei
ABSTRACT: This paper analyses the insurance participation of farmers from the perspective of financial literacy. The results suggest that financial literacy can significantly accelerate the participation of farmers in insurance and the types of participation. In addition, when the farmer is female, highly educated, or younger, financial literacy has a greater effect on the participation of insurance than the male, the low educated, or the older. Meanwhile, when the subjective financial literacy of farmers is consistent with the objective', it is also stronger for the influence of financial literacy on insurance participation and types of insurance participation.